Comparison between s- and d-electron mediated transport in a photoswitching dithienylethene molecule using ab initio transport methods - SANVITO, STEFANO; RUNGGER, IVAN (My University, 2011)
The influence of the electrode's Fermi surface on the transport properties of a photoswitching molecule is investigated with state-of-the-art ab initio transport methods. We report results for the conducting properties of the two forms of dithienylethene attached either to Ag or to nonmagnetic Ni leads. The I-V curves of the Ag/dithienylethene/Ag device are found to be very similar to those reported previously for Au. In contrast, when Ni is used as the electrode material the zero-bias transmission coefficient is profoundly different as a result of the role played by the Ni d bands in the bonding between the molecule and the electrodes. Intriguingly, despite these differences the overall conducting properties depend little on the electrode material. We thus conclude that electron transport in dithienylethene is, for the cases studied, mainly governed by the intrinsic electronic structure of the molecule.
PUBLISHED
Keywords: Physical chemistry; PHOTOCHROMIC REACTION; Nanoscience & Materials